2022
DOI: 10.3389/fimmu.2022.859323
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model Based on PET/CT Radiomics and Clinical Characteristics Predicts Tumor Immune Profiles in Non-Small Cell Lung Cancer: A Retrospective Multicohort Study

Abstract: BackgroundThe tumor immune microenvironment (TIME) phenotypes have been reported to mainly impact the efficacy of immunotherapy. Given the increasing use of immunotherapy in cancers, knowing an individual’s TIME phenotypes could be helpful in screening patients who are more likely to respond to immunotherapy. Our study intended to establish, validate, and apply a machine learning model to predict TIME profiles in non-small cell lung cancer (NSCLC) by using 18F-FDG PET/CT radiomics and clinical characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In addition, in a study about predicting the outcomes of acute ischemic stroke at 6 months after hospital discharge, the AUC of the R-C combined model is 0.868 in the training cohort and 0.890 in the validation cohort, which is significantly higher than that of the clinical or radiomics model (32). Similarly, a machine learning model based on PET/CT radiomics and clinical characteristics predicted the tumor immune microenvironment profiles of nonsmall cell lung cancer, which showed that the R-C combined model has the best performance (33). In our research, the GCS, hematoma volume, midline shift, black hole sign, and Rad-score were employed to build the R-C combined model for predicting the short-term prognosis of HICH patients.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, in a study about predicting the outcomes of acute ischemic stroke at 6 months after hospital discharge, the AUC of the R-C combined model is 0.868 in the training cohort and 0.890 in the validation cohort, which is significantly higher than that of the clinical or radiomics model (32). Similarly, a machine learning model based on PET/CT radiomics and clinical characteristics predicted the tumor immune microenvironment profiles of nonsmall cell lung cancer, which showed that the R-C combined model has the best performance (33). In our research, the GCS, hematoma volume, midline shift, black hole sign, and Rad-score were employed to build the R-C combined model for predicting the short-term prognosis of HICH patients.…”
Section: Discussionmentioning
confidence: 91%
“…The PET/CT-clinical combined model has a significant advantage in predicting the ALK mutation status, with the highest AUC value (0.88) in the test group. In addition, another study has successfully predicted the tumor immune microenvironment phenotype of NSCLC based on the PET/CT-clinical combined model ( 62 ). We summarized the main findings on genotype in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Immunotherapy has led to dramatic changes in the traditional treatment strategies for cancer ( Ansell, 2016 ). However, the efficacy of immunotherapy is mainly affected by the TME phenotype, especially the levels of tumor-infiltrating CD8+ T cells, which are positively correlated with the efficacy of immunotherapy and survival ( Tong et al, 2022 ). T1C is a routine scan sequence for brain tumor patients, and it is more widely used in the diagnosis and evaluation of brain tumor patients at all levels of hospitals than the advanced functional MRI methods, such as DWI, PWI, APT, etc., and is more easily accessible than other scan sequences.…”
Section: Discussionmentioning
confidence: 99%